2016
DOI: 10.1177/1045389x16672562
|View full text |Cite
|
Sign up to set email alerts
|

Modeling approach to evaluating reduction in stress intensity factor in center-cracked plate with piezoelectric actuator patches

Abstract: Active repairs using piezoelectric actuators can play a significant role in reducing the crack damage propagation in thin plate structures. Mode-I crack opening displacement is the most predominant one in tension, and it is responsible for the failure which in turn affects the load carrying capability of the cracked structure. In addition, there are limited studies that investigated the effect of the piezoelectric actuator over mode-I active repair. In this study, the mode-I stress intensity factor for a plate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
24
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 17 publications
(25 citation statements)
references
References 43 publications
1
24
0
Order By: Relevance
“…In fact, the compression stress generated by the piezoelectric actuator counteracted the external loading and resulted in SIF mitigations. The finite element model was validated with the theoretical results through two phases: validation of SIF in cracked plate without piezoelectric patch and validation of the displacement of the piezoelectric actuator operating in extension mode with a certain electric voltage [23]. Furthermore, making specimens with center crack has its own certain limitation, i.e., creating centered cracks in metals.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…In fact, the compression stress generated by the piezoelectric actuator counteracted the external loading and resulted in SIF mitigations. The finite element model was validated with the theoretical results through two phases: validation of SIF in cracked plate without piezoelectric patch and validation of the displacement of the piezoelectric actuator operating in extension mode with a certain electric voltage [23]. Furthermore, making specimens with center crack has its own certain limitation, i.e., creating centered cracks in metals.…”
Section: Resultsmentioning
confidence: 99%
“…In the active repair of a cracked structure, the main objective is to decrease the singular stress at Furthermore, previous works had proved that the thickness ratio and stiffness ratio of piezoelectric patches and host plate have an effect on the reduction of stress intensity factor. Indeed, Abuzaid et al [23] showed that to achieve the best result in reduction in the SIF, it is better to use a thin actuator with relatively high voltage. Fesharaki et al [33] compared the capability of the piezoelectric actuators with different stiffness/thickness ratios in reducing the stress concentration factor in a plate with a hole.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In this work, the lifecycle improvement has been achieved in active mode repair. In d 31 -mode, the effectiveness of active repair is measured in terms of stress intensity factor (SIF) (Abuzaid et al, 2017). It is evaluated by analytical and finite element modelling of a repaired finite plate under mechanical loading.…”
Section: Introductionmentioning
confidence: 99%